Pharmacokinetics and Toxicity Prediction of Lansium domesticum Corr. - Rizaldi, Gusti; Norhayati (MPI (Media Pharmaceutica Indonesiana), 2024)
A wide range of compounds has been isolated from Lansium domesticum Corr. Secondary metabolites are commonly utilised as valuable resources for potential drug for research and development. An exemplary drug candidate must possess efficacy against the therapeutic target, safety, and favourable pharmacokinetic characteristics. The objective of this study was to determine the pharmacokinetic characteristics and toxicity potentials of 23 compounds derived from Lansium domesticum Corr. utilising the pKCSM online tool and the drug-likeness using swissADME online tool. Based on pKCSM prediction, compounds 14 (methyl angolensate) and 22 (7,14(27)-Onoceradiene-3,21-dione) from Lansium domesticum Corr. are identified as having favourable pharmacokinetic properties and are not expected to exhibit mutagenic or hepatotoxic effects. The LD50 values for compounds 14 and 22 were 2.983 and 1.813 (mol/kg), respectively, indicating their lethal dosages. In conclusion, only compound 14 that also met all the Lipinski’s Rule of Five.